USING BLENDED LEARNING TO DEVELOP STUDENTS' SPEAKING SKILLS AT LEVEL B1 (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines using blended learning to develop students' speaking skills at level b1. It conceptualizes speech competence as a complex construct emerging from the interaction of cognitive, linguistic, and affective mechanisms underlying language acquisition and use. Drawing on key theories, including working memory, speech production models, and cognitive load theory, the study highlights the role of cognitive processing (attention, working memory, and conceptualization) in shaping fluency and coherence in oral communication.